Marvell's Ambivalence : Religion and the Politics of Imagination in mid-seventeenth century England. - Yoshinaka, Takashi (Studies in Renaissance literature., 2011)
Andrew Marvell's celebrated poetic ambivalence to the philosophical, political and religious controversies of mid-seventeenth century England is the subject of this book, which includes major new historical readings of his most important lyrics and political verse, incorporating material from hitherto unpublished contemporary manuscripts. It places the poetic imagination of Marvell and his contemporaries - such as John Milton, Henry Vaughan, Abraham Cowley, Margaret Cavendish, William Davenant, and Thomas Fairfax - into the context of the turbulent public events of the time; and demonstrates M.